x=16.3
2006-11-14 09:41:50
·
answer #1
·
answered by Frank R 7
·
1⤊
0⤋
2(x + 7) = 5(x - 7)
2x + 14 = 5x - 35 ... First, distribute the 2 and the 5 respectively.
-3x + 14 = -35 ... Subtract 5x from both sides.
-3x = -49 ... Subtract 14 from both sides
x = 49/3 = 16 1/3 .. Divide both sides by -3.
2006-11-14 17:40:06
·
answer #2
·
answered by Anonymous
·
2⤊
0⤋
2(x+7)=5(x-7)
2x + 14 = 5x -35
2x + 14 +35 = 5x - 35 + 35
2x +49 = 5x
2x + 49 -2x = 5x-2x
49=3x
3x=49
x= 49/3
2006-11-14 17:44:03
·
answer #3
·
answered by Bright One 1
·
1⤊
0⤋
2(x+7) = 5 (x - 7)
2x+14=5x-35
49=3x
x=49/3, or 16 1/3
The first guy doesn't know basic algebra. Neither does the "Ive got Answers" guy a few answers below me.
2006-11-14 17:42:31
·
answer #4
·
answered by Daniel C 4
·
0⤊
0⤋
2x + 14 = 5x - 35
Distribute first:
2x + 14 = 5x - 35
-2x -2x
___
14 = 3x - 35 Combine like terms
-14 -14
3x - 49 Divide by 3 (opposite op.)
__ ___
3 3
x = 16 1/3
2006-11-14 17:49:30
·
answer #5
·
answered by ♥ 6
·
1⤊
0⤋
2(x + 7) = 5(x - 7)
First Distubute the 5 and 2 by multiplying
2x + 14 = 5x - 35
Then Subtract 5x to both sides
2x + 14 - 5x = 5x - 35 - 5x
Leaves us with
-3x + 14 = 35
Then you wanna get rid of the 14.
How do you do that?
Subtract 14 ON BOTH SIDES!
-3x + 14 -14 = 35 - 14
Which leaves us with
-3x = 21
Then Divide -3 on both sides.... Cause of the -3x
-3x = 21
------------
-3 = -3
x = -7
Hope this helps!
2006-11-14 17:46:04
·
answer #6
·
answered by Guy Who Brushes His Teeth* 6
·
0⤊
2⤋
2x+14=5x-35
-5x -5x
-3x+14=-35
-14 -14
-3x=-49
/-3 /-3
x=16 1/3
2006-11-14 17:40:41
·
answer #7
·
answered by musicisme1992 1
·
1⤊
0⤋
2(x+7) = 5 (x - 7)
2x+14=5x-35
49=7x
x=7
2006-11-14 17:37:24
·
answer #8
·
answered by yupchagee 7
·
1⤊
3⤋